Molecular characterisation of rice stripe necrosis virus as a new species of the genus benyvirus - Lozano Potes, Iván; Morales, Francisco José (Springer, 2009)
The complete nucleotide sequences of RNAs 1 and 2 of Rice stripe necrosis virus (RSNV) were determined and compared to the corresponding genomes of all sequenced, rod-shaped plant viruses. The genome organisation of RSNV RNA1 and RNA2 is nearly identical to that of Beet necrotic yellow vein virus (BNYVV) and Beet soil-borne mosaic virus (BSBMV), definitive species of the genus Benyvirus. As demonstrated for BNYVV and BSBMV, the RNA1 of RSNV also encodes a single ORF with putative replicase-associated motifs, which distinguishes benyviruses from all other viruses possessing rod-shaped particles. As described for BNYVV, RNSV RNA-2 also contains six ORFs: the capsid protein gene, the read-through protein gene, a triple gene block gene that codes for three different proteins, and a 17 kDa cysteine-rich protein. RNAs 3 and 4 (or 5 in the case of BNYVV), identified in natural infections of BNYVV and BSBMV, were not detected in any of the 44 RSNV cDNA clones obtained in this investigation. Nevertheless, phylogenetic and amino comparative acid sequence analyses demonstrated that RSNV is more closely related to BNYVV and BSBMV than to any other rod-shaped plant virus characterised to date.